2016
DOI: 10.1108/mf-10-2015-0288
|View full text |Cite
|
Sign up to set email alerts
|

Value of employee satisfaction during the financial crisis

Abstract: Purpose The purpose of this paper is to examine how employee satisfaction affects firm value around the financial crisis. Design/methodology/approach The authors use the 2008 financial crisis as exogenous shocks to firms to mitigate endogenous concern that employee satisfaction and firm value can be jointly determined. The authors compare firm value of two groups of firms: the firms on the Fortune magazine’s list of “100 Best Companies to Work For” and matched firms that are not on the list. The authors empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…All these factors constitute the corporate culture, especially the “trust,” “integrity,” “respect” and “teamwork.” In this respect, Guiso et al (2015) find that “integrity” and “respect” are the most advertised values by organizations only after “innovation.” And half of the companies in their sample were found to be advertising “teamwork.” Inasmuch as these variables capture the corporate culture of a company, it can be surmised that “Best Companies to Work For” proxies for corporate culture. Some of the studies that used the GPTWI’s “Best Companies to Work For” survey as a proxy for great corporate culture and best human resource practices include Edmans (2011), Guiso et al (2015), Carvalho and Areal (2016), Blasi et al (2016), Butler et al (2016) and Cao and Chen (2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these factors constitute the corporate culture, especially the “trust,” “integrity,” “respect” and “teamwork.” In this respect, Guiso et al (2015) find that “integrity” and “respect” are the most advertised values by organizations only after “innovation.” And half of the companies in their sample were found to be advertising “teamwork.” Inasmuch as these variables capture the corporate culture of a company, it can be surmised that “Best Companies to Work For” proxies for corporate culture. Some of the studies that used the GPTWI’s “Best Companies to Work For” survey as a proxy for great corporate culture and best human resource practices include Edmans (2011), Guiso et al (2015), Carvalho and Areal (2016), Blasi et al (2016), Butler et al (2016) and Cao and Chen (2016).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Saadullah and Rezaee (2012) found that the 100 Best Companies to Work For do not yield a better ROE and ROA than their industry peers. Cao and Chen (2016) reported that job satisfaction enhances firm value only when it interacts with financial flexibility and best companies do not have any advantage in post-crisis recovery.…”
Section: Related Literaturementioning
confidence: 99%
“…Since most of crises are hard to predict (which is especially a Black Swan type of crisis, which are by definition impossible to predict), and their duration is usually unknown, there is a great uncertainty about future financial results and the organization will keep costs to a minimum to survive on the market (Cao and Chen, 2016). Hence, the organizations undergoing crisis are usually not able to ensure that all the employees' expectations are met.…”
Section: Work Motivation Job Satisfaction Work Engagement and Job Pmentioning
confidence: 99%
“…It is characteristic for this phase of the crisis that the organization has significant difficulties in planning its activities, due to high unpredictability, dynamic course and extreme speed and intensity (Hackman and Oldham, 1974). In this phase, the organization is primarily focused on a flexible and immediate change of the ways of functioning (Pulakos et al, 2000;Cao and Chen, 2016) so as to ensure the continuity of existence (Cao and Chen, 2016). Unfortunately, in this phase of crisis, employees may find it difficult to adapt to the situation in which the organization finds itself, and the actions they take to prevent losses and achieve results may not be appropriate to the situation (Sotarauta, 2016).…”
Section: Edc Based Model Of Job Performance In Organizations Functionmentioning
confidence: 99%
“…Employees' satisfaction is the key to achieve the organization's goals (William, Schneider, Barbera, and Young, 2012). Cao and Chen (2016) declared that employees' satisfaction is a leverage to enhance work productivity. Companies should be largely benefited when employees' satisfaction is increased (Chi and Gursoy, 2009;Matzler and Renzl, 2007).…”
Section: Introductionmentioning
confidence: 99%